Plyometrics - Faccioni, A.
This literature review has looked at the history, effectiveness and safety of plyometrics. Plyometrics were first developed by Soviet coaches to take advantage of the stretch-shorten cycle. It use was seen as a way to bridge the gap between strength and power. There is still debate on whether plyometrics is more effective in developing power than other forms of exercises. It has been shown that excellent physical improvements can be made when plyometrics are combined with resistance training Many critics of plyometrics suggest that injuries are caused through its use but there have been no studies to confirm this view. To minimise the chance of injury, it is important that coaches gradually allow their athletes to progress from simple to advanced plyometric exercises. It is also important for coaches to monitor that the athlete is using correct technique while performing plyometric exercises. When plyometric exercises are administered properly in a training program, they can be a valuable asset in the improvement of the athlete.